Peranan Camat dalam Pencegahan dan Pengendalian Corona Virus Disease (Covid-19) di Kecamatan Gido, Kabupaten Nias - Beby Beriman Jaya Harefa; Yurial Arief Lubis; Armansyah Matondang (Universitas Medan Area, 2023)
Corona Virus Disease (Covid-19) is an epidemic that has an infectious nature. Covid - 19 first appeared in the city of Wuhan, Hubei Province, China and has spread to 190 countries in the world including Indonesia. Officially, WHO as the world health agency named this virus as Severe Acute Respiratory Syndrome-related Coronavirus-2 (SARS_CoV-2) or Corona Virus Disease 2019 (Covid-19). The Covid-19 virus outbreak is known to have clinical symptoms in human respiration, even to the point of severity causing death. On March 14, 2020 the Indonesian government declared the Covid-19 outbreak a national disaster. As a result of the Covid-19 outbreak, the Indonesian government took strategic steps to prevent wider cases by issuing PSBB and PPKM policies. This policy aims to break the transmission rate of Covid-19. As an issue and problem, Covid-19 has also not escaped the attention of the Gido District government, so this study aims to find out the role of the sub-district head in preventing and controlling Corona Virus Disease (Covid-19) in Gido District, Nias Regency and to find out the obstacles experienced by the Head of Gido subdistrict in the prevention and control of Corona Virus Disease (Covid-19) in Gido District, Nias Regency. This researcher uses a qualitative method that is descriptive in nature, namely to provide a clear picture of the problem under study. Data collection techniques used are observation, interviews and documentation. The results showed that the role of the sub-district head in prevention and control was effective. This is marked by the activeness of the camat in providing advice and outreach and collaborating between various parties such as the Koramil and puskesmas as well as village government officials to jointly prevent the transmission of Covid-19 and provide health facilities for the community such as masks and hand sanitizers. The sub-district head also took firm action against immigrants to self-isolate. The sub-district head also plays a role in monitoring the process of recusing village funds to be diverted to communities affected by Covid-19 so that people can receive social assistance evenly. The inhibiting factor experienced by the sub-district head is that there are still many people who do not understand the dangers of Covid - 19 and the solution for this is that the sub-district head cooperates with the puskesmas to participate in explaining about Covid-19 and how it is transmitted as well as ways to prevent and overcome it.